Public Knowledge, Trust, Attitude, and Behavioral Intention toward the Integration of Jamu into National Health Services - Mohamad Kashuri; Taruna Ikrar (Borneo Journal of Pharmacy, 2026)
The integration of jamu into Indonesia's formal healthcare system remains an important policy issue, particularly in ensuring that regulatory development is matched by public acceptance and behavioral readiness. This study aimed to examine public perceptions of integrating jamu into national health services using a Theory of Planned Behavior (TPB)-informed framework. A quantitative cross-sectional survey was conducted among 300 webinar participants aged 18 years or older using purposive sampling. Data were collected through an anonymous online questionnaire comprising 12 items across four latent constructs: knowledge, trust, attitude, and behavioral intention. The relationships among constructs were analyzed using partial least squares structural equation modeling (PLS-SEM). The results showed that attitude was the strongest predictor of behavioral intention (β = 0.837, p <0.001), while knowledge significantly influenced trust (β = 0.651) and attitude (β = 0.248), and trust also significantly influenced attitude (β = 0.486). The model explained 70% of the variance in behavioral intention, indicating substantial explanatory power. These findings suggest a coherent behavioral pathway in which knowledge and trust strengthen attitude, which in turn drives public intention to support the integration of jamu into formal healthcare services. The study concludes that successful integration depends not only on regulatory readiness but also on strengthening public knowledge, trust, and attitudes toward traditional medicine. However, the findings should be interpreted cautiously because the sample was non-random and relatively digitally literate. Future studies should include more diverse populations and use longitudinal or mixed-method approaches to support evidence-based integration policies.